Superantigen protocols - Krakauer, Teresa (Humana Press, 2003)
The publication focuses on clinical protocols used for the study of superantigens. Intended for professional public.
Methods in molecular biology, ISSN 1064-3745 Volume 214
Keywords: Clinical Laboratory Techniques; Superantigens; klinické laboratorní techniky; alergologie a imunologie; T-Lymphocytes; klinické protokoly; Clinical Protocols; T-lymfocyty; superantigeny